Long-wavelength UV-LEDs and charge management in the detection of gravitational waves in space - Jia, Yuandong; Zhang, Yinbowen; Wang, Suwen; Chai, Guozhi; Zhang, Zemin; Zhang, Yi; Li, Hongxin; Huang, Shuanglin; Huo, Hongqing; Li, Zongfeng; Lau, Yun Kau (Frontiers in Astronomy and Space Sciences, 2025)
For the charge management system in gravitational wave detection missions, a continuous discharge strategy is considered by continuously illuminating a test mass (TM) with weak light in such a way to strike a balance between the charging and discharging rates and at the same time avoids the requirement for frequent activation of charge measurements. Extending earlier experimental work on a simple parallel plate model, the present study adopts a more advanced inertial sensor model that replicates the surface properties and work function of a cubical TM in a space-based sensor. This model is used to investigate a bipolar charge management system that utilizes UV-LEDs with peak wavelengths of 269 nm, 275 nm, 280 nm, and 295 nm that are longer than the standard 255 nm commonly employed for direct TM illumination. Experimental results indicate that the 275 nm UV-LED achieves optimal performance, maintaining the TM potential closer to zero and at the same time accommodates both rapid discharge and continuous discharge strategies. The present work provides useful input in the future study of system design and optimization for the charge management system.